Antibodies to human fetal erythroid cells from a nonimmune phage antibody library - Huie, Michael A. (The National Academy of Sciences, 2001)
The ability to isolate fetal nucleated red blood cells (NRBCs) from the maternal circulation makes possible prenatal genetic analysis without the need for diagnostic procedures that are invasive for the fetus. Such isolation requires antibodies specific to fetal NRBCs. To generate a panel of antibodies to antigens present on fetal NRBCs, a new type of nonimmune phage antibody library was generated in which multiple copies of antibody fragments are displayed on each phage. Antibody fragments specific for fetal NRBCs were isolated by extensive predepletion of the phage library on adult RBCs and white blood cells (WBCs) followed by positive selection and amplification on fetal liver erythroid cells. After two rounds of selection, 44% of the antibodies analyzed bound fetal NRBCs, with two-thirds of these showing no binding of WBCs. DNA fingerprint analysis revealed the presence of at least 16 unique antibodies. Antibody specificity was confirmed by flow cytometry, immunohistochemistry, and immunofluorescence of total fetal liver and adult RBCs and WBCs. Antibody profiling suggested the generation of antibodies to previously unknown fetal RBC antigens. We conclude that multivalent display of antibodies on phage leads to efficient selection of panels of specific antibodies to cell surface antigens. The antibodies generated to fetal RBC antigens may have clinical utility for isolating fetal NRBCs from maternal circulation for noninvasive prenatal genetic diagnosis. Some of the antibodies may also have possible therapeutic utility for erythroleukemia.